Exploration of the Relationship of Sleep Quality in Patients with Diabetic Retinopathy, Villahermosa Tabasco: Exploración de la Relación de la Calidad del Sueño en Pacientes con Retinopatía Diabética, Villahermosa Tabasco - Espinoza-Anguiano, Tirsa A. (2021)
Introduction: In recent decades, there has been growing evidence suggesting that too little or too much sleep is associated with adverse health outcomes, including type 2 diabetes. There is a close association between diabetes and diabetic retinopathy (DR), so it is reasonable to assume that sleep may also have associations with DR. Objective: To explore the relationship between the perception of sleep quality and the degree of diabetic retinopathy in patients with type 2 Diabetes Mellitus treated at a 3rd level dophthalmological care service. Results: Significant correlations were found in: diastolic and systolic blood pressure (0.429), triglycerides and total cholesterol (0.707), glycosylated hemoglobin (HbA1c) and glycemia (0.561), Epworth sleepiness scale (ESS Score) and age (0.394) , ESS Score and weight (0.365), extended STOP questionnaire (Stop Bang) and age (0.317), Stop Bang and weight (0.579), Stop Bang and ESS Score (0.452), insomnia severity index (ISI Score) and Stop Bang (0.460). Although the reduced sample size limited the results in the associations by subgroups in the study, a trend towards an elevation of the ESS score can be seen in the subgroup of patients who reported sleeping 8 hours or more. Conclusions: Although the trends are not statistically significant, the authors consider that this finding is congruent with the state of the art on the subject of sleep and metabolic condition of retinopathic diabetic patients (increased trend of ESS score reported in the subgroup of 8 or more hours sleep), it will be necessary to explore this phenomenon in more detail and in a larger number of patients.